Tác động của tích hợp chuỗi cung ứng đến hiệu suất logistics của các doanh nghiệp dịch vụ logistics: Vai trò trung gian của năng lực quản lý logistics và điều tiết của môi trường logistics - Nguyen Thanh, Hung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The study analyses the impact of supply chain integration directly on logistics performance and indirectly through logistics management capabilities, including demand management capability, operation management capability and resource management capability, as well as the moderating impact of the enterprise logistics environment on this relationship. Using the partial least squares method to test the research sample of 392 logistics service providers (LSP) in the Southeast region, it shows that supply chain integration, including three components of internal integration, customer integration and logistics collaborator integration, has a positive impact on the logistics performance of enterprises, and this impact level will increase when combined with logistics management capabilities. The more complex the logistics environment of LSPs is, the more they tend to integrate the supply chain, thereby improving logistics management capabilities and enhancing the enterprise’s logistics performance. Thus, the study provides some managerial implications to improve the logistics performance of LSPs from the perspective of supply chain integration.